Pengaruh corporate social responsibility disclosure terhadap kinerja keuangan dengan reputasi sebagai variabel moderasi - Fidela Raniah Sawity; Arumega Zarefar; Mayla Khoiriyah; Raja Adri Satriawan Surya; Atika Zarefar; Ulfa Afifah; Sinta Ramaiyanti (Akuntansi dan Teknologi Informasi, 2024)
This study aims to determine the effect of corporate social responsibility disclosure (CSRD) on firm financial performance with corporate reputation as a moderation variable. It focuses on primary and secondary sector companies listed on the IDX in 2014-2022. The dependent variable is firm financial performance, measured using return on assets (ROA). The independent variable, corporate social responsibility disclosure, is measured using the GRI G4. The corporate reputation as moderation variable is measured using the number of awards obtained by the company. The control variables used are company size, leverage, and cash flow. The sampling technique used purposive sampling and obtained as many as 143 companies. This research uses quantitative data, and the method used is regression analysis using the STATA application. The results of this study show that CSRD has a significant positive effect on firm financial performance. These findings provide practical guidelines for companies, stating that it is essential for a company to implement CSRD practices and have a good impact on the company's financial performance, thereby guiding companies in their CSR initiatives.